Neonatal adrenal hemorrhage presenting as late onset neonatal jaundice - Qureshi Umar; Ahmad Nisar; Rasool Akhter; Choh Suhail (Wolters Kluwer Medknow Publications, 2009)
Clinical manifestations of adrenal hemorrhage vary depending on the degree and rate of hemorrhage, as well as the amount of adrenal cortex compromised by hemorrhage. We report here a case of neonatal adrenal hemorrhage that presented with late onset neonatal jaundice. The cause of adrenal hemorrhage was birth asphyxia.